Intravenous access in children. Issue 6 (June 2020) - Bennett, James; Cheung, Mary
Abstract: Establishing intravenous access in children can be challenging for the healthcare professional and distressing for the patient and their family. Choosing the most appropriate intravenous vascular access is key to improving short-term and long-term care in patients. Children requiring prolonged or repeated intravenous access are at higher risk of venous catheter associated complications, which may result in progressive loss of patent vasculature. Poor planning though multiple, episodic attempts at intravenous access without careful consideration for the type, indication and duration of the venous catheter may limit treatment. Increasingly hospitals have specialist teams, from various disciplines, to insert peripheral and central venous catheters. Correct selection of site and optimal technique may minimize failed attempts at securing intravenous access, improve the experience of paediatric patients and improve care.